Plants and predators, partners in crop protection - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Of the various ways in which the agricultural research community can help farmers to ensure that the food grown for the consumer's plate is not consumed by insect pests before it leaves the field, biological control is one of the most attractive....